Dosimetric Verification of Gamma Passing Rate for Head and Neck Cases Treated with Intensity Modulated Radiation Therapy (IMRT) Treatment Planning Technique (Baghdad Science Journal, 2021)
Each Intensity Modulated Radiation Therapy (IMRT) plan needs to be tested and verified before any treatment to check its quality. Octavius 4D-1500 phantom detector is a modern and qualified device for quality assurance procedure. This study aims to compare the common dosimetric criteria 3%/3 mm with 2%/2 mm for H&N plans for the IMRT technique. Twenty-five patients with head and neck (H&N) tumor were with 6MV x-ray photon beam using Monaco 5.1 treatment planning software and exported to Elekta synergy linear accelerator then tested for pretreatment verification study using Octavius 4D-1500 phantom detector. The difference between planned and measured dose were assessed by using local and global gamma index (GI) analysis method at threshold 10%. The DD/DTA criteria are performed with 3%/3 mm and 2%/2 mm. A significant difference is shown between the measured and calculated point dose for the treatment plans. A comparison made between the gamma passing rate between the 2%/2 mm and 3%/3 mm shows a significant difference for local and global which shows that the 2%/2 mm are more sensitive to dose variation than 3%/3 mm. The total monitor unit (MU) shows a negative linear relationship with both criteria and %GP types. A significant correlation is shown between the total MU and global %GP at 2%/2 mm criterion. The conclusion of the study indicates that 2%/2 mm criterion is more sensitive to the dose distribution changes than the 3%/3 mm. The total number of monitor units should be taken into consideration during the planning of H&N tumors using the IMRT plans.